Pendidikan anti korupsi: Konstruksi moral feeling dan tindakan moral kewarganegaraan mahasiswa dalam mencegah kecurangan akademik - dayanah, warda mujibah (Maliki Interdisciplinary Journal, 2026)
Anti-corruption education in Islamic higher education institutions is a strategic instrument to break the chain of misconduct from an early stage. The research gap lies in the lack of understanding of how the construction of moral feeling influences students’ moral civic action in preventing academic corruptive behavior, such as cheating. This study aims to explore the relationship between the dimensions of moral feeling and students’ civic action as a framework for developing effective anti-corruption education. The research design utilizes an explanatory quantitative survey approach with a sample of active university students in Indonesia. Data collection instruments used a Likert scale questionnaire that met the criteria for validity and reliability (Cronbach’s Alpha > 0.7). Data analysis was performed using descriptive statistics and simple linear regression. The results indicate a significant positive relationship between moral feeling and students’ moral civic action within the framework of anti-corruption education (p < 0.05). Every one-point increase on the moral feeling scale correlates with a 0.5-point increase in students’ moral civic action. Theoretical implications suggest that the anti-corruption education curriculum in higher education must integrate moral affective strengthening to foster national character with high integrity.